2015
DOI: 10.1074/jbc.m115.684217
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Monolignol 4-O-Methyltransferase with High Selectivity for the Condensed Lignin Precursor Coniferyl Alcohol

Abstract: Background: Guaiacyl lignin dominates the polymer's condensation, therefore, negatively affecting plant cell wall's digestibility. Results: A promiscuous O-methyltransferase was incrementally evolved to constrain its substrate specificity to guaiacyl lignin precursors. Conclusion:The enzyme with nine amino acid substitutions is functionally specialized for selectively methylating the condensed lignin precursors. Significance: The obtained enzyme is a candidate for specifically altering lignin structure to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Directed evolution is also a powerful tool for engineering protein domain specificity over cognate target residues or for developing enzymes with different activities (Figure b). An example comes from Cai et al, who in 2015 showed how directed evolution of the plant enzyme monolignol 4- O -methyltransferase could be used to change its substrate specificity with consequent ability to improve lignin digestion and conversion . More recently, Dai et al.…”
Section: Applications In Biological Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Directed evolution is also a powerful tool for engineering protein domain specificity over cognate target residues or for developing enzymes with different activities (Figure b). An example comes from Cai et al, who in 2015 showed how directed evolution of the plant enzyme monolignol 4- O -methyltransferase could be used to change its substrate specificity with consequent ability to improve lignin digestion and conversion . More recently, Dai et al.…”
Section: Applications In Biological Engineeringmentioning
confidence: 99%
“…An example comes from Cai et al, who in 2015 showed how directed evolution of the plant enzyme monolignol 4-Omethyltransferase could be used to change its substrate specificity with consequent ability to improve lignin digestion and conversion. 121 More recently, Dai et al engineered the histidine methyltransferase SETD3, changing its target specificity from histidine to lysine. 122 By comparing the active site of SETD3 with the ones of the lysine methyltransferases SETD6 and LSMT, the authors individuated two amino acids, Asn55 and Trp273, responsible for histidine specificity.…”
Section: ■ Applications In Biological Engineeringmentioning
confidence: 99%
“…The change of a few residues at the OMT-I substrate-binding site could modify their regioselectivity and substrate specificity. Other rational and semi-rational designs have been performed with CbIEMT1, increasing its substrate scope [ 37 ] or generating a highly specific enzyme [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two tested MOMT variants exhibit different effects on lignin and phenolic biosynthesis in planta. MOMT4, which favours methylating the S-type sinapyl alcohol over the G-type coniferyl alcohol in vitro (Bhuiya and Liu, 2010;Zhang et al, 2012), suppresses more S lignin deposition in transgenic rice, resulting in large reductions in the S/G lignin ratios as determined by both thioacidolysis (Figure 5c) and 2D NMR (Figure 6c), whereas expressing MOMT9, a variant that more prefers modifying G monomers over S monomers in vitro due to its smaller substrate binding pocket (Cai et al, 2015), leads to a less prominent effect on the S/G lignin ratio reductions (Figures 5c and 6c), and concomitantly the sole production of the soluble 4-O-methylated FA-derived metabolites (Figure 2). These results demonstrate that both MOMT variants function properly in grass species and are in line with their in vitro structural and catalytic properties.…”
Section: Discussionmentioning
confidence: 99%